2022
DOI: 10.1177/02724316221099871
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Attachment Priming on State Attachment Security in Middle Childhood: The Moderating Roles of Trait Attachment and State Attachment Volatility

Abstract: Recent studies showed that attachment security can change within persons, suggesting that there might be an interplay between a rather stable (trait) and rather variable (state) part of attachment. The study’s first aim was to investigate whether attachment priming could influence the level of state attachment. The second aim was to explore possible moderators explaining individual differences in the relation between state attachment responses to attachment versus neutral primes. This can shed light on individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Longitudinal studies have shown that secure base script knowledge is relatively stable over time (Vaughn et al, 2006; Waters, Ruiz, & Roisman, 2017; Waters et al, 2022; Waters, Facompré, et al, 2021) and continuity in observed relations between secure base script knowledge and parental sensitivity and discipline might therefore be expected. At the same time, secure base script knowledge can be modified in response to attachment-related experiences (Bosmans et al, 2020, 2022; Cuyvers et al, 2023). Furthermore, Waters et al (2019) demonstrated that stressful life events predicted change in adolescents’ knowledge of the secure base script.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies have shown that secure base script knowledge is relatively stable over time (Vaughn et al, 2006; Waters, Ruiz, & Roisman, 2017; Waters et al, 2022; Waters, Facompré, et al, 2021) and continuity in observed relations between secure base script knowledge and parental sensitivity and discipline might therefore be expected. At the same time, secure base script knowledge can be modified in response to attachment-related experiences (Bosmans et al, 2020, 2022; Cuyvers et al, 2023). Furthermore, Waters et al (2019) demonstrated that stressful life events predicted change in adolescents’ knowledge of the secure base script.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have demonstrated that secure base script knowledge is relatively stable over time (Vaughn et al, 2006; Waters et al, 2017, 2022; Waters, Facompré, et al, 2021). However, secure base script knowledge is not set in stone but can be modified through attachment-related experiences (Bosmans et al, 2020, 2022; Cuyvers et al, 2023; see also Waters et al, 2019). In addition, adults’ knowledge of the secure base is shaped (in part) by the quality of early caregiving experiences (Nivison et al, 2021; Schoenmaker et al, 2015; Steele et al, 2014; Vaughn et al, 2016; Waters et al, 2017).…”
mentioning
confidence: 99%
“…The promise is that eventually 'this information can be fed back to participants with personalised recommendations that may range from getting more sleep to contacting a health care professional' (Schweizer et al, 2019). This approach is not much different from the use of the phone app diary method across 14 days in our study with Cuyvers et al (2022) on state and trait attachment in 9-to 13-year-old children. However, this study is not deemed a CS project.…”
Section: Participant Involvement In Data Collectionmentioning
confidence: 99%
“…In addition, thinking style could also be an important moderating variable in the relationship between analytic processing and creativity. Numerous studies have shown that individuals’ traits, tendencies, and styles can influence their psychological and behavioral performance, along with temporary priming manipulations, such as trait power and state power ( Schmidt-Barad and Uziel 2020 ), trait mindfulness and state mindfulness ( Egan et al 2018 ), trait attachment and attachment priming ( Cuyvers et al 2022 ), and chronic regulatory focus and situational regulatory focus, etc. ( Krishna et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%